(untitled) (Journal of Hama University, 2022)
The research aims to use the Torrance Test for Creative Thinking, the formal section, to study the differences between deaf and ordinary students in creative thinking, on samples of ordinary basic education stage two students and deaf basic education students who are in the deaf care centers in the city of Latakia. Of (550) students of the basic education stage for the academic year (2020-2021) in the schools of the city of Latakia, whose ages range from (13-15) years, the sample was randomly drawn, and the sample consisted of (148) deaf students present at the Center for Special Education for Hearing Impairment in Latakia, and the results of the study showed the following: 1- There are statistically significant differences between (males and females) in creative thinking skills according to the gender variable. 2- There are no statistically significant differences at the level of significance between the mean scores of students on the Torrance Test for Creative Thinking, according to the category variable. 3- There are no statistically significant differences at the level of significance between the mean scores of students on the Torrance Test for Creative Thinking, according to the grade variable.